“Being it no matter what anyone else think about it:” Combating Gender Bias with Nontraditional Literature in an Urban Elementary Classroom - Martin James Wasserberg (Networks: An Online Journal for Teacher Research, 2012)
Gender stereotypes pervade children’s literature. This action research project sought to alter stereotypical perceptions of gender roles held by a classroom of students in an urban elementary school through the introduction of nontraditional literature. Results suggested that some stereotypical perceptions could be altered through utilization and discussion of such literature.